Urogenital schistosomiasis during pregnancy is associated with low birth weight delivery: analysis of a prospective cohort of pregnant women and their offspring in Gabon. Issue 1 (January 2017) - Mombo-Ngoma, Ghyslain; Honkpehedji, Josiane; Basra, Arti; Mackanga, Jean Rodolphe; Zoleko, Rella Manego; Zinsou, Jeannot; Agobe, Jean Claude Dejon; Lell, Bertrand; Matsiegui, Pierre-Blaise; Gonzales, Raquel; Agnandji, Selidji Todagbe; Yazdanbakhsh, Maria; et al.
Graphical abstract: Highlights: Estimated 40 million women of childbearing age currently suffering from schistosomiasis worldwide. There is not yet any systematic information about the impact of urogenital schistosomiasis on pregnancy. Urogenital schistosomiasis infection is common amongst pregnant women in rural central Africa. Urogenital schistosomiasis leads to low birth weight delivery. This finding calls for the development of public health programmes for pregnancy in endemic regions of Africa. Abstract: An estimated 40 million women of childbearing age suffer from schistosomiasis. Animal models indicate a deleterious effect of maternal schistosomiasis on pregnancy outcomes. To date there is a lack of epidemiological evidence evaluating schistosomiasis-related morbidity in pregnancy. This study was designed to describe the impact of urogenital schistosomiasis on pregnancy outcomes in a highly endemic region of central Africa. Pregnant women attending antenatal clinics in Fougamou and Lambaréné, Gabon, were consecutively screened for the presence of Schistosoma haematobium eggs in diurnal urine samples. Maternal and newborn characteristics assessed at delivery were compared between infected and uninfected mothers. The impact of maternal schistosomiasis on low birth weight and preterm delivery was assessed using logistic regression analysis. Urogenital schistosomiasis was diagnosed in 103 (9%) of 1115 pregnant women. Maternal age was inversely associated with the prevalence of urogenital schistosomiasis, with a higher burden amongst nulliparous women. Low birth weight was more common amongst infants of S. haematobium -infected mothers. This association was unaffected by controlling for demographic characteristics, gestational age and Plasmodium infection status (adjusted Odds Ratio 1.93; 95% confidence interval: 1.08–3.42). Other risk factors associated with low birth weight delivery were underweight mothers (adjusted Odds Ratio 2.34; 95% confidence interval: 1.12–4.92), peripheral or placental Plasmodium falciparum infection (adjusted Odds Ratio 2.04; 95% confidence interval: 1.18–3.53) and preterm birth (adjusted Odds Ratio 3.12; 95% confidence interval: 1.97–4.96). Preterm delivery was not associated with S. haematobium infection (adjusted Odds Ratio 1.07 95% confidence interval: 0.57–1.98). In conclusion, this study indicates that pregnant women with urogenital schistosomiasis are at an increased risk for low birth weight deliveries. Further studies evaluating targeted treatment and prevention programmes for urogenital schistosomiasis in pregnant women and their impact on delivery outcomes are warranted.